ANALYSIS OF DIFFERENT FACTORS IMPACT ON PARTICULATE MATTER FORMATION DURING THE REFUSED DERIVED FUELS COMBUSTION - Nosek, Radovan; Sramka, Michal; Kantová, Nikola Čajová (International Multidisciplinary Scientific GeoConference SGEM, 2024)
The process of burning alternative materials such as refused derived fuels is an important topic in current scientific research and industry. Emissions and particulate matters are formatted during the combustion of refused derived fuels (RDF) and it is important to identify the ways of their reduction. This manuscript analyses the influence of factors such as fuel fraction and fuel moisture on particulate matter (PM) concentrations. The findings can assist to better understand the impact of individual factors on air quality. The main goal of this work is to conduct an experiment in laboratory conditions to determine the optimal conditions for the RDF combustion. Nine samples of RDF with the moisture from 0% to 6.5% were combusted in the experimental setup. Further measurements analyzed the effect of fuel fraction and PM concentration. The particulate matters were measured by TSI Scanning Mobility Particle Sizer and Aerodynamic Particle Sizer during the experiments. The concentration of particulate matters decreased up to 50.1% in the case of fractions ≤0.5 mm. The analysis of moisture effect shows that higher content of water has a negative effect on the mass concentration of PM. The greatest decrease in PM mass concentration by up to 69.4% was recorded for the RDF 7 sample when the moisture content changed from 6.18% to 0.0%. The obtained results show links between PM concentrations and mentioned conditions.